The Effect of Tahajud Prayers on the EQ (Emotional Quotient) of New Santriwati at At-Tauffiqiyah Islamic Boarding School Sumenep - Asyila Aulia Putri; Sari Luthfiyah; Miadi Miadi; Sri Utami; Mazlinda Musa (International Journal of Advanced Health Science and Technology, 2025)
New students at boarding schools often experience culture shock which can affect their EQ (Emotional Quotient). Tahajud prayer as a sunnah worship is believed to have an influence on increasing EQ (Emotional Quotient) through deeper spiritual habituation. A new santri who makes tahajud prayer a routine worship will have a good EQ (Emotional Quotient). In line with the purpose of this study to determine the effect of tahajud prayer on the EQ (Emotional Quotient) of new female santri at Pondok Pesantren At-Taufiqiyah Sumenep. This study used a cross- sectional observational design with a sample of 43 new female santri selected using simple random sampling technique. The results of the analysis of this study using the ordinal regression analysis test obtained a p-value of 0.01 <0.05 which means that there is an effect of tahajud prayer on the EQ (Emotional Quotient) of new female santri at the At-Taufiqiyah Islamic Boarding School Sumenep. The implementation of tahajud prayer can affect the EQ (Emotional Quotient) of new female santri, because by regularly implementing tahajud prayer and parenting factors from parents and administrators tend to have a better level of self-awareness, emotional control, motivation, empathy, and social skills compared to those who rarely do it.